2018
DOI: 10.1371/journal.pone.0190923
|View full text |Cite
|
Sign up to set email alerts
|

A new pathological scoring system by the Japanese classification to predict renal outcome in diabetic nephropathy

Abstract: Background and objectivesThe impact of the newly proposed pathological classification by the Japan Renal Pathology Society (JRPS) on renal outcome is unclear. So we evaluated that impact and created a new pathological scoring to predict outcome using this classification.Design, setting, participants, & measurementsA multicenter cohort of 493 biopsy-proven Japanese patients with diabetic nephropathy (DN) were analyzed. The association between each pathological factor—Tervaert’ and JRPS classifications—and renal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 36 publications
2
25
0
2
Order By: Relevance
“…Note that, among the known factors 23 , PS was the only factor that served as a predictor of the progression of 2-year ACR in patients with microalbuminuria ( n = 87). Receiver operating characteristic (ROC) curve analysis in the U-CARE Study, showing comparison of known factors 23 . f AUC-ROC using known factors (0.713) and adjusted with PS (0.751) ( n = 87).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Note that, among the known factors 23 , PS was the only factor that served as a predictor of the progression of 2-year ACR in patients with microalbuminuria ( n = 87). Receiver operating characteristic (ROC) curve analysis in the U-CARE Study, showing comparison of known factors 23 . f AUC-ROC using known factors (0.713) and adjusted with PS (0.751) ( n = 87).…”
Section: Resultsmentioning
confidence: 99%
“…We next performed multiple regression analysis. To evaluate, we built three models: model 1 (crude model); model 2 (adjusted by known factors: age, gender, BMI, SBP, HbA1c, log (eGFR)) 23 ; and model 3 (full model; adjusted by model 2 plus other clinical factors in Supplementary Table 4, i.e., DBP, ALT, total cholesterol (TC), triglyceride (TG), high-density lipoprotein (HDL) and UA). Multiple regression analysis revealed that ACR was the only factor that significantly correlated with PS among all models (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the prevalence of DM in Chinese adults was reported to be 0.67% in 1980, then gradually increased to be 10.9% in 2013, and that for prediabetes was 35.7%. [8,9] Second, the DKD research did have new breakthroughs in some fields, such as histopathological diagnosis, [1013] therapeutic agents, [1417] and biomarkers for early screening. [2,1821] Third, with the development of internet technology, massive medical data were easier to be obtained and shared.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, although diabetic nephropathy is a common disease, its pathophysiology is largely unclear. Therefore, we examined the association between pathological changes in diabetic nephropathy and clinical outcomes [55][56][57][58][59][60][61][62]. Other examples can be found in many areas, such as in the areas of treatment of polycystic liver disease [63,64], amyloidosis [65][66][67][68], and severe ischemic limb treatment [69][70][71][72].…”
Section: Challenges For Intractable Kidney Disease: Importance Relevmentioning
confidence: 99%